Time-variable, event-based walking control for biped robots. (18th April 2018) - Wahrmann, Daniel; Wu, Yizhe; Sygulla, Felix; Hildebrandt, Arne-Christoph; Wittmann, Robert; Seiwald, Philipp; Rixen, Daniel
Most walking controllers for biped robots are based on a synchronized phase-based structure, where trajectories are executed following predefined timing constraints. This inherent fixed time dependency makes humanoid robots extremely susceptible to irregularities in terrain compared to their biological counterparts. We present an event-based control strategy which incorporates a time-variable phase to help deal with unexpected early and late contact situations. It results in an improved robustness against such scenarios, as shown by simulation results of our robot Lola .